2005
DOI: 10.1007/s00170-004-2438-3
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based collaborative product development chain for networked product development

Abstract: Product development in the manufacturing industry has been facing unprecedented challenges brought about by everchanging global and competitive market conditions as well as changing individual customer demands. As manufacturing enterprises become more specialized, they need to communicate and work concurrently on a large volume of product data covering their factories, sub-contractors as well as suppliers. The collaboration and cooperation between enterprises is changing from a supply chain based on material f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Hill 2002, Zhang and Zhou 2004, Yujun et al 2005. Most of those proposed, such as: video conferencing; immersive virtual reality; and online application sharing, support the co-operation and communication effort between collaborating companies, with the ultimate goal of making individual participation in CNs easy.…”
Section: Literature Review 21 Collaboration Networkmentioning
confidence: 97%
“…Hill 2002, Zhang and Zhou 2004, Yujun et al 2005. Most of those proposed, such as: video conferencing; immersive virtual reality; and online application sharing, support the co-operation and communication effort between collaborating companies, with the ultimate goal of making individual participation in CNs easy.…”
Section: Literature Review 21 Collaboration Networkmentioning
confidence: 97%
“…IT driven new PD was identified as one of the main factors that reduced both development cycle time and development costs (Laurindo and Carvalho, 2005). The majority of studies identified in the literature focus on proposing IS to improve collaboration with suppliers and enable information exchange via the internet (Lee et al, 2003;Rodriguez and Al-Ashaab, 2005;Yujun et al, 2006). Although various tools and techniques have been introduced to assist firms in achieving better performance when launching new products, it was identified that in practice many tools and techniques are not utilised effectively (Yeh et al, 2010).…”
Section: Related Researchmentioning
confidence: 99%
“…The main reason is that the technology of CAD and CAPP were developed independently, they can not exchange and transfer information each other automatically [2][3][4]. In this system, the integrated CAX interface based PDM is used to realize information share, the same database is used to avoid replicate data entries and transformation.…”
Section: Introductionmentioning
confidence: 99%